2017
DOI: 10.1038/ncomms15933
|View full text |Cite|
|
Sign up to set email alerts
|

Growth of organic crystals via attachment and transformation of nanoscopic precursors

Abstract: A key requirement for the understanding of crystal growth is to detect how new layers form and grow at the nanoscale. Multistage crystallization pathways involving liquid-like, amorphous or metastable crystalline precursors have been predicted by theoretical work and have been observed experimentally. Nevertheless, there is no clear evidence that any of these precursors can also be relevant for the growth of crystals of organic compounds. Herein, we present a new growth mode for crystals of DL-glutamic acid mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 44 publications
(73 reference statements)
1
48
0
Order By: Relevance
“…The exact nature of this high binding affinity is unknown, although the exceedingly high binding force revealed in our AFM analysis of CC interaction with cholesterol-containing lipid domain may offer some clue. The extraction of cholesterol from the membrane may mimic the precursor condensation onto the crystalline surface in the typical growth of organic crystals ( 57 ), which may be translated into a force exerted on the plasma membrane. This notion, however, requires vigorous experimental verification, as alternative explanation may exist.…”
Section: Discussionmentioning
confidence: 99%
“…The exact nature of this high binding affinity is unknown, although the exceedingly high binding force revealed in our AFM analysis of CC interaction with cholesterol-containing lipid domain may offer some clue. The extraction of cholesterol from the membrane may mimic the precursor condensation onto the crystalline surface in the typical growth of organic crystals ( 57 ), which may be translated into a force exerted on the plasma membrane. This notion, however, requires vigorous experimental verification, as alternative explanation may exist.…”
Section: Discussionmentioning
confidence: 99%
“…When LCPs are applied for controlling the organization of organic and inorganic materials, liquid‐solid and liquid‐liquid interfaces are crucial factors. Recently, crystallization studies of D,L‐glutamic acid identify the attachment of hydrated nanoscopic assemblies to pre‐formed crystals, followed by the release of hydration water, structural relaxation and transformation to 2D crystals . However, on silica surface, the nanoscopic assemblies do not transform easily.…”
Section: Pathways To Complex Organizations Of Mattermentioning
confidence: 98%
“…Traditionally, crystallization is considered to follow the classical theory based on monomer-bymonomer addition. However, it has recently been shown that nonclassical crystallization occurs in many systems: 21,48,50,[77][78][79][80][81][82] Nucleation can have a two-step mechanism that differs from that described by classical nucleation theory; 77,83-87 particles larger than monomers / ions can participate in the growth of crystals; 30,39,40 an oriented attachment (OA) mechanism has also been identified, in which nanocrystals coalesce to form the bulk crystal. 34,[36][37][38]88 The term "crystallization by particle attachment (CPA)" is now used to denote crystallization processes that are dominated by particles other than monomers / ions.…”
Section: Nonclassical Crystallization Of Cof-5mentioning
confidence: 99%